Factors influencing resilience in patients with advanced cancer: A cross-sectional study - Pimonpan Niamhom; Tipaporn Wonghongkul; Jindarat Chaiard; Chomphoonut Srirat (Belitung Raya Foundation, Indonesia, 2023)
Background: Advanced cancer and its treatments lead to various detrimental impacts on patients. Resilience is an important ability to adapt to such adversity, but there is limited information about its influencing factors, specifically in patients with advanced cancer. Objective: This study aimed to examine the influence of social support, depression, anxiety, hope, optimism, spiritual well-being, religious belief,and hardiness on resilience among adults with advanced cancer. Methods: This cross-sectional research used multi-stage sampling to select 288 participants from a university hospital and three tertiary hospitalsin northern Thailand. Data were collected using a demographic data collection form, the Hospital Anxiety and Depression Scale (HADS), the Thai version of the Social Support Questionnaire (SSQ), the Herth Hope Index (HHI), Life Orientation Test-Revised (LOT-R), Buddhist Belief Questionnaire, Health-Related Hardiness Scale (HRHS), and Connor-Davidson Resilience Scale (CD-RISC), from February 2021 to February 2022. Data were analyzed using descriptive statistics, Pearson correlation, and regression analysis. Results: Depression (r = -0.47, p <0.01) and anxiety (r = -0.39, p <0.01) had a significant negative relationship with resilience. Spiritual well-being(r = 0.74, p <0.01), hope (r = 0.67, p <0.01), religious belief (r = 0.53, p <0.01), optimism (r = 0.40, p <0.01), social support (r = 0.33, p <0.01), and hardiness (r = 0.21, p <0.01) had significant positive relationships with resilience. Only hope (β = 0.29, p <0.01) and spiritual well-being (β = 0.59, p<0.01) together influenced resilience by 64.70%. Conclusion: Spiritual well-being and hope are crucial to resilience in patients with advanced cancer. Nurses should provide spiritual support to strengthen patients’ ability to adapt successfully to life with advanced cancer.